A view from the Brow of the Hill. Partial reflections on autonomy, models and priorities. (2nd November 2018) - Daffra, Emanuela
ABSTRACT: Lately, since the 'riforma Franceschini', we saw an increasing growth of the pursuit of an effective model to run Italian public museums since February 2016, after having worked more than 20 years as superintendent of artistic and historic heritage in Milan, and being assistant and director of the Pinacoteca di Brera in 2015, I became for 1 year director of the newborn Fondazione Accademia Carrara in Bergamo, going successively back for few months to Brera. Thanks to the twofold experience, the former more about the private side, the latter watching from the outside a freshly reformed museum, I believe I can compare the two models and highlight the positive and negative aspects of both of them. However, this comparison underlines possible common obstacles that should not be taken for granted, obstacles caused by the lack of expert staff when it comes to defining the layout of the museum (economic, governance, organogram) and by the scarce clarity of the main aims of an itinerary that will be unavoidably long but compulsory.